Enhancing interprofessional education and practice: Development and implementation of a new graduate-level course using the international classification of functioning, disability, and health. Issue 3 (3rd May 2016) - Nguyen, Tram; Fayed, Nora; Gorter, Jan Willem; MacDermid, Joy
ABSTRACT: Since the introduction of the World Health Organization's International Classification of Functioning, Disability and Health (ICF), there is increasing awareness among health professionals to consider a biopsychosocial approach to patients' health and functioning. Although diffusion of the ICF as a concept is widely recognized, application of the ICF within health education and practice requires attention, training, and support. This article describes the development and implementation of a new graduate-level course using the ICF to assist health professionals and graduate trainees in rehabilitation. The innovation behind this course is its focus on application of the ICF in research and practice through a combination of peer support and instructor mentorship. The value of the ICF for interprofessional education, research, and practice includes promotion of a broad perspective to health, application of theory in practice, and enhanced communication and collaboration in healthcare.